Prevalence and Side Effects of Energy Drink Consumption among Medical Students at Umm Al-Qura University, Saudi Arabia - Naif A. Bawazeer; Najmah A. AlSobahi (University Library System, University of Pittsburgh, 2013)
Background: Energy drinks are freely available at markets and shops on the university campus without regulation or proper education regarding its side effects. The caffeine amount within energy drinks is high and could become an addictive substance or cause intoxication. Therefore, this study aims to assess the prevalence of energy drink consumption and its reported side effects among medical students.  Methods:A total number of 257 medical students from Umm Al-Qura University completed a questionnaire about energy drinks that was administrated electronically from September through November, 2012.  Results:Out of the 257 participants, 27.2% (n=70) reported consuming at least one energy drink per month, with 61.5% (n=48) being males. Males consume significantly more energy drinks than females (p=0.0001). The students consumed energy drinks to get energy in general (32.8%) and while studying for exams or finishing a project (31.4%). Other reasons given include, lack of sleep (12.8%), just to be like friends (11.4%), or driving (8.5%). Heart palpitations are the most common side effect in our sample (20%), followed by insomnia (10%), headache and tremors (5.7%), nausea and vomiting (4.2%) and nervousness (2.8%).  Conclusion: Energy drinks consumption is common practice among medical students and the main reason cited for consumption is the need for energy during general activities. Approximately one-third of the consumers manifested some side effect after consumption. We recommend the need to create public awareness about energy drinks. Further studies are recommended to assess the educational level of students consuming energy drinks, about the dangerous side effects.